Rancang Bangun Mesin Extruder Filamen 3D Printing - Firmansyah, Iqbal; Sateria, Angga; Pranandita, Nanda (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The 3D printer filament extruder is a machine used to melt and extrude filament for 3D printing processes. Thermoplastics are one type of plastic commonly used in filament production due to their durability, strength, and easy to shape, making them a preferred material for filament manufacturing. Filament is produced through an extrusion process using a machine equipped with a high-temperature heating system to shape the filament. The aim of this research is to design, construct, and test a 3D printing filament extruder to produce filament. This research produces a 3d printing filament extruder machine with a vertical position that uses a DC motor as a driving mechanism, while chains and sprockets are used to reduce rotation and increase rotational torque. Based on the results of the trials conducted, the barrel temperature of 250°C and the screw rotation speed of 5 RPM which produces a filament diameter that is close to the standard for filament use with an average filament diameter of 1.97 mm.